ONLINE FOOD WASTE MANAGEMENT SYSTEM - oketcho Solomon (My University, 2024)
Online Food waste management has become an increasingly critical issue worldwide. According to the Food and Agriculture Organization (FAO, 2011), approximately one-third of the food produced for human consumption is lost or wasted globally, amounting to about 1.3 billion tons per year. This waste occurs throughout the food supply chain, from initial agricultural production down to final household consumption. Effective food waste management is crucial not only for reducing environmental impacts, such as greenhouse gas emissions from landfills but also for addressing food insecurity and improving resource efficiency. In recent years, various strategies have been implemented to mitigate food waste, including food donation programs, improved supply chain logistics, and consumer education campaigns. Technological advancements, such as smart packaging and waste-to-energy technologies, also offer promising solutions (Parfitt, Barthel, & Macnaughton, 2010). Despite these efforts, the problem persists, indicating a need for more integrated and innovative approaches to food waste management.